A rare combination of Ebstein's anomaly with left ventricular outflow tract obstruction. Issue 3 (10th February 2023) - Sun, Chenchen; Sun, Wei; Zhang, Yanting; Li, Yuman; Xie, Mingxing
Abstract: We describe a rare case of Ebstein's anomaly (EA) combined with left ventricular outflow tract obstruction in a 54‐year‐old man that was accurately identified by echocardiography, cardiac magnetic resonance imaging (CMR). The imaging result was ultimately validated by surgery. We emphasize the clinical importance of using echocardiography and CMR together to provide a thorough, noninvasive explanation of these results.